ASPEK RELIGIUSITAS, SANKSI DAN KEPATUHAN PAJAK KENDARAAN BERMOTOR DI INDONESIA - Riri Zelmiyanti (AKUNTABILITAS, 2017)
The purpose of this research is to explore more thoroughly and detail about the influence of the value of religiosity, sanctions and compliance of vehicle tax in Indonesia. The research on tax compliance has been widely studied, but still not much study it from religiosity side and tax sanctions. Previously research is mostly done by personal taxpayer, companies and home industries. This research is conducted by survey method, distribution of questionnaries to vehicle taxpayer. Quantity of questionnaries which analyzed is 120 copies. Analysis tool is using “Structural Equation Modelling-Partial Least Square (SEM-PLS)” by WarpPLS 5.0 software. Based on result of research can be conclude that religiosity have significant influence to tax compliance. P- value <0.05 ?=0.25 so H1 can be proven. This research is also prove that sanctions have influence to tax compliance. P-value < 0.05 ?=0.42 so H2 can be proven. Influence of value of religiosity and sanction to tax compliance is about 33% and the rest is influenced by other variables. Therefore the considerasion to improve tax compliance from aspect of religiosity needs to be developed.